Immobilization of Glucose Oxidase on Modified-Carbon-Paste-Electrodes for Microfuel Cell - Laksmi Ambarsari; Inda Setyawati; Rini Kurniasih; Popi Asri Kurniatin; Akhiruddin Maddu (Universitas Gadjah Mada, 2016)
Glucose oxidase (GOx) is being developed for many applications such as an implantable fuel cell, due to its attractive property of operating under physiological conditions. This study reports the functional immobilization of glucose oxidase onto polyaniline-nanofiber-modified-carbon-paste-electrodes (GOx/MCPE) as bioanodes in fuel cell applications. In particular, GOx is immobilized onto the electrode surface via a linker molecule (glutaraldehyde). Polyaniline, synthesized by the interfacial polymerization method, produces a morphological form of nanofibers (100-120 nm) which have good conductivity. The performance of the polyaniline-modified-carbon-paste-electrode (MCPE) was better than the carbon- paste-electrode (CPE) alone. The optimal pH and temperature of the GOx/MCPE were 4.5 (in 100 mM acetate buffer) and 65 °C, respectively. The GOx/MCPE exhibit high catalytic performances (activation energy 16.4 kJ mol-1), have a high affinity for glucose (Km value 37.79 µM) and can have a maximum current (Imax) of 3.95 mA. The sensitivity of the bioelectrode also was high at 57.79 mA mM-1 cm-2.